2015
DOI: 10.1212/wnl.0000000000002085
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stroke in retinal vein occlusion

Abstract: The present study provides new evidence that patients with incident RVO are at increased risk of stroke just after RVO occurrence. Immediate risk evaluation and proper treatment of stroke risk factors in patients with RVO are needed to reduce stroke-related mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Recent studies have shown that after RAO and RVO, patients have an increased risk of ischemic stroke and myocardial infarction, particularly during the first weeks after the occlusion. [ 8 , 16 , 17 ] , [ 18 ] It is unclear whether this is an epiphenomenon explained by diseases sharing similar risk factors (eg, CAD is a strong risk factor for both IS and RAO, and atherosclerosis is a risk factor for myocardial infarction, ischemic stroke and RAO), or by sharing the same pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that after RAO and RVO, patients have an increased risk of ischemic stroke and myocardial infarction, particularly during the first weeks after the occlusion. [ 8 , 16 , 17 ] , [ 18 ] It is unclear whether this is an epiphenomenon explained by diseases sharing similar risk factors (eg, CAD is a strong risk factor for both IS and RAO, and atherosclerosis is a risk factor for myocardial infarction, ischemic stroke and RAO), or by sharing the same pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…18 While RVO is not an independent risk factor for cardiovascular or stroke-related mortality, patients with RVO have a high risk of hypertension (48%-85%) and an increasing trend in incident strokes. 17,1922, 24, 27 A recent longitudinal study showed an increased risk of stroke in individuals with RVO versus the comparison group (16.8% vs 10.7%). 23 Central RVO has been associated with increased mortality that is likely attributable to systemic cardiovascular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A validation study comparing diagnoses between the database and patients' medical records showed an overall positive predictive value of the diagnosis of 83.4% . Detailed information regarding the NHIS and the database has been reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…9 Detailed information regarding the NHIS and the database has been reported elsewhere. 8,[10][11][12][13][14][15][16][17] Databases from anonymous sources are open to any researchers whose study protocol has been approved by the Official Review Committee of the NHIS. The present study was approved by the Institutional Review Board (IRB) of the Seoul National University Bundang Hospital (IRB No.…”
Section: Study Populationmentioning
confidence: 99%